Gerontechnology: Understanding Older Adult Information and Communication Technology Use - Birkland, Johanna (Emerald Publishing Limited, 2019)
This book presents a typology that explains the diversity of ICT usage seen in older adults. It examines older adult use of everyday Information and Communication Technologies (ICTs) across multiple life contexts (work, family, leisure, and community) allowing readers to understand how the growing aging population will use ICTs in their daily lives. The author offers a useful framework to practitioners (both in community based and institutional settings) who work with older adults to fully understand how technological interventions will be taken up.